The Pacific Solution as Australia Policy towards Asylum Seeker and Irregular Maritime Arrivals (IMAs) in John Howard Era - Hardi Alunaza; Ireng Maulana; Adityo Darmawan Sudagung (Jurnal Ilmiah Hubungan Internasional, 2018)
This research is attempted to answer the question of why John Howard used the Pacific Solution as Australian policy towards Asylum Seekers and Irregular Maritime Arrivals (IMAS). By using the descriptive method with a qualitative approach, the researchers took a specific interest in decision-making theory and sovereignty concept to analyze the phenomena. The policy governing the authority of the Australian Government in the face of the Asylum Seeker by applying multiple strategies to suppress and deter IMAs. The results of this research indicate that John Howard used Pacific Solution with emphasis on three important aspects. First, eliminating migration zone in Australia. Second, building cooperation with third countries in the South Pacific, namely Nauru and Papua New Guinea in shaping the center of IMAs defense. On the other hand, Howard also made some amendments to the Migration Act by reducing the rights of refugees. Immigrants who are seen as a factor of progress and development of the State Australia turned into a new dimension that threatens economic development, security, and socio-cultural.